Public submissions on the Uganda National Biotechnology and Biosafety Bill, 2012 reveal potential way forward for Uganda legislators to pass the bill - Masiga, Clet Wandui (Frontiers in Bioengineering and Biotechnology, 2012)
The Cartagena Protocol on Biosafety to the Convention on Biological Diversity is an internationally binding instrument addressing issues of biosafety. Biosafety refers to the need to protect human health and the environment from the possible adverse effects of the products of modern biotechnology. Accordingly, all countries to the convention are required to put in place regulatory mechanisms to enhance the safety of biotechnology in the context of the Convention’s overall goal of reducing all potential threats to biological diversity, while taking into account the risks to human health. Therefore, each country party to the convention has its own procedures to enact laws to guide the safe use of biotechnology. In Uganda, the process involves the drafting of the bill by the first parliamentary counsel, approval by cabinet, first reading at the parliament, committal to the responsible parliamentary sessional committee, tabling of the bill for public hearing, consultations, and final approval. In Uganda, the Committee on Science and Technology is responsible for the Biosafety Bill. In March 2013, the Committee tabled the bill for public hearing and submissions from public institutions. There were comments supporting the passage of the Bill and comments in objection. The reasons for objection are mainly due to precaution, speculation, lack of knowledge about biotechnology and biosafety, and alleged influence from biosafety entrepreneurs. This article reviews these public views, revealing controversy and possible consensus to pass the bill.
Keywords: Biotechnology; Biosafety; Genetically modified; Parliament; Legislation; Entrepreneur